Thursday

March 26, 2015

March 26, 2015

Posted by **sharday** on Thursday, February 23, 2012 at 11:41pm.

- algebra -
**MathMate**, Friday, February 24, 2012 at 8:29amSubstitution:

Rewrite each as:

6x=3y+18

6x=-12-3y

Since they are both 6x, then

3y+18=-12-3y

=>

6y=-30

y=-5

and

x=(3*(-5)+18)/6=1/2

By elimination (easier in this case)

Add the two equations:

6x-3y + 6x+3y = 18 -12

12x=6

x=1/2

-3y=18-6*(1/2)

y=-5

**Answer this Question**

**Related Questions**

Algebra 1 - bobpursey, In this problem you helped me with earlier: Solve using ...

Substitution Method-Plz help - Use the Substitution method to solve the system ...

Algebra Help!! - solve using the substitution method. y= 5 - 3x 4x + y= 7

Algebra - Solve using substitution method 3x+8y=20 x=24-7y

Algebra - x-2y=.9 4x-3y=13.1 Solve using the substitution method.

Algebra - 4x+y=42 6x-5y=50 Solve using the substitution method.

Algebra - Solve using the substitution method. 0.3x+0.2y=5,0.5x+0.4y=11

algebra - using the substitution method how do you solve y=-1/3x y+2x=5

Algebra - solve using substitution method 3x-5y=61 3x-y=17

algebra - x+3y=-10 7x-5y=34 solve using substitution method